Guitar Zero
On the eve of his fortieth birthday, scientist Gary Marcus decided to fulfil a lifelong dream and learn to play the guitar, investigating how humans \'make\' music and how anyone of any age might master a new skill. In a quest that takes him from Suzuki classes to guitar gods, Marcus discovers the best ways to train your brain and your body. He also brings insight into the question, What counts as a life well lived? A groundbreaking look at the origins and allure of music, Marcus\'s journey is also an empowering tale of the mind\'s plasticity and its ability to grow throughout life.